1971
DOI: 10.1126/science.172.3990.1357
|View full text |Cite
|
Sign up to set email alerts
|

Evoked Potential Correlates of Auditory Signal Detection

Abstract: A long-latency comnponent of the averaged evoked potential recorded from the human scalp varied in close relationship with subjects' perceptual reports in an auditory signal detection task. Detected signals evoked potentials several times larger than did undetected signals, falsely reported signals, or correctly reported nonsignals. The threshold signal intensity at which detection perfornmance exceeded chance levels was identical with concurrently obtained electro-physiological measures of threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
192
6
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(219 citation statements)
references
References 21 publications
20
192
6
1
Order By: Relevance
“…Particular attention has been paid to a transient evoked potential called the P3 or P300 (for example, see refs. [19][20][21][22]. Under auditory stimulus conditions analogous to our experiments, the magnitude of the P3 exhibited dependence on trial category similar to what we have observed with fMRI 19,20 .…”
Section: Discussionsupporting
confidence: 89%
“…Particular attention has been paid to a transient evoked potential called the P3 or P300 (for example, see refs. [19][20][21][22]. Under auditory stimulus conditions analogous to our experiments, the magnitude of the P3 exhibited dependence on trial category similar to what we have observed with fMRI 19,20 .…”
Section: Discussionsupporting
confidence: 89%
“…Some might consider this paradigm as suboptimal in the present investigation. We would note, however, that the MMN is indeed reliably elicited under both active and passive listening conditions (eg NÀÀtĂ€nen et al, 1978;Ritter et al, 1992) and that later components such as N200/P300 are only observed during active paradigms and furthermore may not be a pure index of sensory discrimination abilities (Hillyard et al, 1971). Such things being said, it will clearly be worthwhile for future investigations to examine the MMN under passive conditions as well as when target stimuli are either closer to the deviant's frequency and/or vary in their duration; the latter being a well-established means of dissociating effects specific to the N1 component from those specific to MMN generation.…”
Section: Discussionmentioning
confidence: 75%
“…For instance, research using stimulus recognition tasks revealed that reported confidence in recognition is associated with increased P3 amplitudes [28]. Furthermore, attentional blink studies demonstrate that the P3 amplitude systematically varied with conscious recognition [17].…”
Section: Discussionmentioning
confidence: 99%